Alaska subsistence : a National Park Service management history - Norris, Frank B. (Frank Blaine), 1950-; United States. National Park Service. Alaska System Support Office. (Anchorage, Alaska : Alaska Support Office, National Park Service, U.S. Dept. of the Interior, 2002)
"This study is a chronicle of how subsistence management in Alaska has grown and evolved"--P. viii. "September 2002." Shipping list no.: 2003-0059-P. Includes bibliographical references (p. 284-292) and index. 1. Alaska Native and rural lifeways prior to 1971 -- 2. The National Park Service and the subsistence question -- 3. Subsistence in Alaska's parks, 1910-1971 -- 4. The Alaska lands question, 1971-1980 -- 5. Initial subsistence management efforts -- 6. Managing Alaska's subsistence program, 1985-1989 -- 7. The federal assumption process, 1989-1993 -- 8. NPS subsistence management activities, 1990-present -- 9. The subsistence fishing question -- 10. Concluding remarks. "This study is a chronicle of how subsistence management in Alaska has grown and evolved"--P. viii. Mode of access: Internet.